2010
DOI: 10.1093/jxb/erq349
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of expression dynamics of WOX homeodomain transcription factors during somatic embryogenesis in Vitis vinifera

Abstract: Different cultivars of Vitis vinifera vary in their potential to form embryogenic tissues. The WUSCHEL (WUS)-related homeobox (WOX) genes have been shown to play an important role in coordinating the gene transcription involved in the early phases of embryogenesis. The expression dynamics of 12 VvWOX genes present in the V. vinifera genome in embryogenic and other tissues of 'Chardonnay' were analysed. In order to understand the influence of WOX genes on the somatic embryogenic process, their expression profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
2
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 41 publications
4
79
2
4
Order By: Relevance
“…Our results differ from reports on the behavior of WOX3 transcript accumulation for other species, in which the transcripts have been observed to accumulate in advanced stages of embryonic development and to diminish significantly in the phases prior to germination (Haecker et al, 2004;Gambino et al, 2011). There is evidence to support the argument that WOX3 malfunction can be related to malformations of the aerial part, as this gene is associated with early leaf formation (Nakata et al, 2012;Lin et al, 2013;Shimizu et al, 2009;Vandenbussche et al, 2009).…”
Section: Accumulation Of Wox3 Transcripts In Somatic and Zygotic Embrcontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results differ from reports on the behavior of WOX3 transcript accumulation for other species, in which the transcripts have been observed to accumulate in advanced stages of embryonic development and to diminish significantly in the phases prior to germination (Haecker et al, 2004;Gambino et al, 2011). There is evidence to support the argument that WOX3 malfunction can be related to malformations of the aerial part, as this gene is associated with early leaf formation (Nakata et al, 2012;Lin et al, 2013;Shimizu et al, 2009;Vandenbussche et al, 2009).…”
Section: Accumulation Of Wox3 Transcripts In Somatic and Zygotic Embrcontrasting
confidence: 99%
“…patterns show greater presence of transcripts in the more advanced stages of embryonic development (Gambino et al, 2011;Haecker et al, 2004;Lin et al, 2013). Previous reports have demonstrated that over-expression and under-expression of WOX1 can cause alterations in plant phenotype due to the fact that this gene is associated with the organization of cellular division in leaves, organs and carpels (Lin et al, 2013;Vandenbussche et al, 2009;Zhang et al, 2011).…”
Section: Wox1 Transcript Accumulation In Somatic and Zygotic Embryos mentioning
confidence: 89%
See 3 more Smart Citations